Functional connectivity in obsessive-compulsive disorder and its subtypes. Issue 7 (23rd May 2020) - Ravindran, Arun; Richter, Margaret; Jain, Tania; Ravindran, Lakshmi; Rector, Neil; Farb, Norman
Abstract: Background: Obsessive-compulsive disorder (OCD) is an anxiety disorder with significant morbidity whose pathophysiology is not fully understood. Neuroimaging studies have characterized OCD in terms of elevated striatal and prefrontal reactivity to emotion provocation. This neural model may be informed by investigation of functional connectivity in OCD, identifying alterations in how sensory information is integrated into frontostriatal regions. Methods: The current study employed functional magnetic resonance imaging (fMRI) to compare neural activity and connectivity in 31 OCD patients (12 washing and 19 checking subtypes) and 17 healthy volunteers in an emotion provocation paradigm using visual stimuli. Results: OCD status was associated with hyper-activation of the posterior cingulate (PCg) in response to emotion provocation. Additionally, OCD patients demonstrated elevated PCg functional connectivity with the visual cortices and frontostriatal regions. Exploratory analyses suggested that stimulus-provoked activity and connectivity was elevated for checking subtypes in motor cortices, and elevated in washing subtypes in the anterior insula and orbitofrontal cortex. Conclusions: The PCg's role in moderating connectivity between the visual cortex and frontolimbic regions is muted in OCD, consistent with the PCg's suggested role in regulating attention towards emotional stimuli. Exploratory analyses suggest distinct PCg connectivity profiles in OCD subtypes, with checking linked to motor activation, but washing linked to a network supporting emotional salience. The study was not powered to fully investigate the effects of medication, patients often endorsed secondary symptom subtypes that muddied washing/checking distinctions, and the emotion provocation paradigm was of limited intensity compared to life stressors.